High‐Temperature Equation of State of FeH: Implications for Hydrogen in Earth's Inner Core. Issue 5 (9th March 2022) - Tagawa, Shoh; Gomi, Hitoshi; Hirose, Kei; Ohishi, Yasuo
Abstract: While hydrogen is one of plausible major light elements in the core, the high‐temperature equation of state (EoS) of Fe‐H alloy has not been experimentally examined to the core pressure range. Here we measured the volume ( V ) of non‐magnetic (NM) face‐centered cubic (fcc) FeH at high pressure and temperature ( P‐T ) to 142 GPa and 3660 K in a laser‐heated diamond‐anvil cell and obtained its P‐V‐T EoS. An increase in the lattice volume of Fe per H atom, Δ V H, determined as functions of P and T is found to be substantially smaller than the volume of metallic H that has been used to estimate H concentration in Fe‐H alloy. The Δ V H is almost identical between fcc and double hexagonal close‐packed phases in the NM state, suggesting that it may be applicable to hcp. The extrapolation of Δ V H to inner core conditions indicates its maximum H content to be 0.8–0.9 wt%. Plain Language Summary: FeH is an important component in terrestrial planetary cores, and its equation of state (EoS) is useful to estimate their H concentrations from observed densities. The high‐ T EoS of FeH has not been examined experimentally to the Earth's core pressure range (>136 GPa) because of difficulties in high P ‐ T experiments on H‐bearing systems. The face‐centered cubic (fcc) structure is known to be a stable form of FeH under a wide P ‐ T range. Also, our first‐principles calculations showed that fcc FeH loses the local spin moment above ∼40 GPa. The present experiments determined the volume of fcc FeH to 142 GPa and 3660 K and obtained its EoS for the non‐magnetic state. The lattice volume of Fe expands by incorporating H in its interstitial site. Our data show that Δ V H, the volume increase per H atom, is similar between the fcc and double hexagonal close‐packed phases in the absence of magnetism and may be applicable to hcp. Such Δ V H obtained as functions of P and T predicts the density of FeH x under inner core conditions and gives the possible compositional range of the Fe‐H‐Si‐S inner core. Key Points: We obtained the P ‐ V ‐ T equation of state of FeH based on volume measurements up to 142 GPa and 3660 K using a diamond‐anvil cell Δ V H, the volume increase of Fe by H atom, was determined as functions of P and T, enabling estimates of the H content in non‐magnetic FeH x We estimate the maximum H content in the inner core and discuss the possible compositional range of the Fe‐H‐Si‐S inner core